Matching of Pumped and Laser Mode Volumes Inside a Diode Side-pumped Solid-state Laser - Quy, Ho Quang; Luu, Mai Van; Sau, Vu Ngoc (Communications in Physics, 2012)
The condition to match the pumped-volume's width with the laser mode-volume's waist in a diode four side pumped solid-state laser is analyzed by numeric solutions of the approximation equation. As a result, the dependences of pumped volume's width on pumping diode parameter and laser mode volume's waist on cavity parameter were found. Such a matching condition was simultaneously determined by cavity, pumping beam and laser rod parameters. %Key words: Laser diode side-pumped, Coherent pump, Excitred active center distribution.